Biogeography of microbial communities in high‐latitude ecosystems: Contrasting drivers for methanogens, methanotrophs and global prokaryotes - Seppey, Christophe, V W; Cabrol, Léa; Thalasso, Frederic; Gandois, Laure; Lavergne, Céline; Martinez‐cruz, Karla; Sepulveda‐jauregui, Armando; Aguilar‐muñoz, Polette; Astorga‐españa, María, Soledad; Chamy, Rolando; Dellagnezze, Bruna, Martins; Etchebehere, Claudia; et al. (Environmental Microbiology, 2023)
International audience Methane-cycling is becoming more important in high-latitude ecosystems as global warming makes permafrost organic carbon increasingly available. We explored 387 samples from three high-latitudes regions (Siberia, Alaska and Patagonia) focusing on mineral/organic soils (wetlands, peatlands